Lowering Cardiovascular Disease Risk for People with Severe Mental Illnesses in Primary Care: A Focus Group Study. - Alexandra Burton; David Osborn; Lou Atkins; Susan Michie; Ben Gray; Fiona Stevenson; Hazel Gilbert; Kate Walters (PLoS ONE)
Background People with severe mental illnesses die early from cardiovascular disease. Evidence is lacking regarding effective primary care based interventions to tackle this problem. Aim To identify current procedures for, barriers to, and facilitators of the delivery of primary care based interventions for lowering cardiovascular risk for people with severe mental illnesses. Method 75 GPs, practice nurses, service users, community mental health staff and carers in UK GP practice or community mental health settings were interviewed in 14 focus groups which were audio-recorded, transcribed and analysed using Framework Analysis. Results Five barriers to delivering primary care based interventions for lowering cardiovascular risk in people with severe mental illnesses were identified by the groups: negative perceptions of people with severe mental illnesses amongst some health professionals, difficulties accessing GP and community-based services, difficulties in managing a healthy lifestyle, not attending appointments, and a lack of awareness of increased cardiovascular risk in people with severe mental illnesses by some health professionals. Identified facilitators included involving supportive others, improving patient engagement with services, continuity of care, providing positive feedback in consultations and goal setting. Conclusion We identified a range of factors which can be incorporated in to the design, delivery and evaluation of services to reduce cardiovascular risk for people with severe mental illnesses in primary care. The next step is determining the clinical and cost effectiveness of primary care based interventions for lowering cardiovascular risk in people with severe mental illnesses, and evaluating the most important components of such interventions.